Condições percebidas sobre a organização do trabalho docente e crenças de autoeficácia de professores do ensino médio - Weber, Sônia Suzana Farias (2020)
In this research, we seek to characterize the factors related to teaching performance with possible influences on the motivation and self-efficacy of teachers from the State Public School Network of Teaching / RS working in high school, in the State Public School Network (REPE), from Santa Maria / RS, in answer to the research problem: What approximations can be established between the beliefs of self-efficacy of high school teachers in the organization of teaching work and the time of professional practice? The sources of information were: (1) subjects: teachers working in the Public High Schools (EPEM) of REPE, in Santa Maria/RS, scope of the 8th CRE; (2) documents: School Regulations and Pedagogical Political Projects. In spaces of this type: (1) didactic-pedagogical planning sessions (individual and collective), (2) pedagogical meetings of teachers for study, organization and planning, held at EPEM. The tools for collecting information: (1) questionnaires, (2) focus group type interview; for organization, treatment and information analysis, we use: (1) script for textual analysis of documents, (2) theory based on data, for the interview and mixed questionnaire, with open questions and Likert scale (1 to 5 points); we applied 150 questionnaires to teachers of the three EPEM, in two ways: (1) we use google forms, sending by e-mail; (2) physical, delivered by hand; getting feedback from only 57 questionnaires, via google forms; we conducted a mixed interview (focus group) with 12 teachers, in an EPEM. As research findings, in relation to teachers' statements, it is evident that: the highest percentage of teachers (68.4%) is distributed in the Experimentation or Diversification phase of the professional career, whose time of experience is 07 to 25 years. The beliefs they have in the ability to do their work are related to the length of professional experience and job satisfaction at school. The reasons given for carrying out the teaching work, refer to the time they dedicate to their studies, to solve the problems faced in the class, to the positive changes in the students' behavior, to satisfaction with the conditions at school for the exercise of the profession, to the valorization by students of activities or tasks scheduled for learning, making decisions to face difficulties and solving problems, and engaging in the search for solutions to different daily challenges. The relationship established between professional life cycles and the motivation to develop teaching work, whose experiences, in the different stages of the teaching professional career, contribute to the redefinition of the profession, are: stability, diversity, expansion and professional commitment, strengthening empathy for students, providing satisfaction, professional and human growth. The elements that characterize teachers' self-efficacy beliefs in planning and developing their work, constitute the set of everyday practices, essences in the teaching function, such as: plan teaching and learning strategies, considering the differences and individual times of students; choice of the most appropriate methods and strategies, with different approaches and explanations; conducting classes, calmly and serenely; help students overcome doubts, lack of courage and desire for studies; plan spaces for questions and clarification of doubts; work together (colleagues and teaching team); believe that your work is effective; commit to the school's curriculum proposal; establish good working relationships with the management team, students and fellow teachers; present willingness and spontaneity to develop teaching activities. Thus, the motivation for teaching work, begins by planning to teach students significant learning. We conclude that the teachers' self-efficacy is in the disposition and satisfaction for the organization, planning and promotion of the activities, being the beliefs of selfefficacy, indispensable conditions to engage and commit to the teaching function in the performance of professional activities.